Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1177/2050312120945138
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of oncogenic and non-oncogenic human papillomavirus is associated with human immunodeficiency virus infection in Kenyan women

Abstract: Objectives: Cervical cancer is caused by persistent infection with oncogenic, or “high-risk” types of human papillomaviruses, and is the most common malignancy in Kenyan women. A longitudinal study was initiated to investigate factors associated with persistent human papillomavirus detection among HIV-infected and HIV-uninfected Kenyan women without evidence of cervical dysplasia. Methods: Demographic/behavioral data and cervical swabs were collected from HIV-uninfected women (n = 82) and HIV-infected women (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…They were participants in a prospective cohort study investigating biological, behavioral, and environmental risk factors for oncogenic HPV persistence, a part of the East African Consortium for Human Papillomavirus and Cervical Cancer in Women Living with HIV/AIDS [ 16 ]. Details of study enrollment procedures have been previously published [ 11 ]. Briefly, women aged 18 to 60 years living within 30 km of Eldoret presenting for screening at the CCSP were asked to participate in the study if they had a normal visual inspection with acetic acid (VIA) of the uterine cervix that day.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They were participants in a prospective cohort study investigating biological, behavioral, and environmental risk factors for oncogenic HPV persistence, a part of the East African Consortium for Human Papillomavirus and Cervical Cancer in Women Living with HIV/AIDS [ 16 ]. Details of study enrollment procedures have been previously published [ 11 ]. Briefly, women aged 18 to 60 years living within 30 km of Eldoret presenting for screening at the CCSP were asked to participate in the study if they had a normal visual inspection with acetic acid (VIA) of the uterine cervix that day.…”
Section: Methodsmentioning
confidence: 99%
“…Structured face-to-face interviews of the participants by trained researchers were conducted at enrollment to capture social, behavioral, and biological information, including age, marital status, educational level, home ownership, walking distance to the local clinic, number of lifetime sexual partners, and age of first sex [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A cohort was enrolled in 2015 to 2016 consisting of 116 HIV-infected and 106 HIV-uninfected women aged 18 to 45 years, with normal VIA that day at the AMPATH Cervical Cancer Screening Program (CCSP), located at MTRH, in Eldoret, Kenya [ 34 ]. Studies conducted as part of in Project 1 indicated that oncogenic and non-oncogenic HPV types were detected more often among HIV-infected women compared with HIV-uninfected women, and that persistent HPV (one-year persistence or two-year persistence) was more often detected among HIV-infected women than HIV-uninfected women [ 35 ]. In addition, a longer duration of ART use was associated with significantly reduced risk of HR-HPV detection and persistence [ 36 ].…”
Section: The Consortium Version 1: “Hpv and Cervical Cancer In Kenyan...mentioning
confidence: 99%
“…Characteristics of age, marital status, education, home ownership, walking distance to health care, number of lifetime sex partners, and age of first sex with a p-value <0.20 from univariate analyses were selected to include in the model. LR-HPV (low-risk HPV):HPV 6,11,40,42, 54, 55, 61, 62, 64, 71, 72, 81, 83, 84, CP6108.…”
mentioning
confidence: 99%